2015
DOI: 10.1128/jvi.03143-14
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Nuclear Trafficking Signals in Pseudorabies Virus pUL31

Abstract: The herpesviral nuclear egress complex (NEC), consisting of pUL31 and pUL34 homologs, mediates efficient translocation of newly synthesized capsids from the nucleus to the cytosol. The tail-anchored membrane protein pUL34 is autonomously targeted to the nuclear envelope, while pUL31 is recruited to the inner nuclear membrane (INM) by interaction with pUL34. A nuclear localization signal (NLS) in several pUL31 homologs suggests importin-mediated translocation of the protein. Here we demonstrate that deletion or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 50 publications
7
38
1
Order By: Relevance
“…To further test the function of the predicted NES, a plasmid expressing an EYFP dimer (dEYFP) fused to the C-terminus of aa246-254 was constructed, and aa246-254-dEYFP also showed similar subcellular localization to aa231-254-EYFP, confirming that the predicted NES of pUL31 is nonfunctional and that the functional NES of UL31 may depend on its spatial conformation. These results are conflict with those of Paßvogel and colleagues [13]. This can probably be explained by subtle differences in experimental design.…”
Section: Introductioncontrasting
confidence: 74%
See 1 more Smart Citation
“…To further test the function of the predicted NES, a plasmid expressing an EYFP dimer (dEYFP) fused to the C-terminus of aa246-254 was constructed, and aa246-254-dEYFP also showed similar subcellular localization to aa231-254-EYFP, confirming that the predicted NES of pUL31 is nonfunctional and that the functional NES of UL31 may depend on its spatial conformation. These results are conflict with those of Paßvogel and colleagues [13]. This can probably be explained by subtle differences in experimental design.…”
Section: Introductioncontrasting
confidence: 74%
“…However, it is still an endemic problem in many countries, although efforts to eradicate PRV in many countries have made great progress [14]. The UL31 protein (pUL31), a PRV-encoded late protein, is composed of 271 amino acid (aa) residues [3], is among the first and best characterized pUL31 homologues [3,8,13]. Herpes simplex virus 1 (HSV-1) UL31 [1,3,7,10,11,[15][16][17][18][19] and Epstein-Barr virus (EBV) BFLF2 [4,6,9], the homologues of PRV UL31, have also been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior appears to be a beta herpesvirus phenomenon, although there is some indication of similar behavior in psuedorabies virus (Klupp et al, 2007). There are reports that transiently co-expressed UL50 and UL53 (and their homologues) are capable of deforming the INM (Gonnella et al, 2005; Hagen et al, 2015; Klupp et al, 2007; Lorenz et al, 2015; Milbradt et al, 2012; Passvogel et al, 2015; Reynolds et al, 2001; Sharma et al, 2014; Zeev-Ben-Mordehai et al, 2015), which has begun to be explained through structural analysis of these proteins (as reviewed in (Bigalke and Heldwein, 2015)). Our results (see Figure 4F) confirmed this behavior in the absence of p53 during transient expression.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our immunofluorescent localization, Dalmonte et al used immuno-EM at late times pi to determine that UL53 was located within large invaginations (IINMs) within the nucleus (Dal Monte et al, 2002). In addition, transient expression of the equivalent PrV proteins (UL31/UL34) produces "speckles", which have been determined to be "vesicle formation in the perinuclear space" (Hagen et al, 2015; Passvogel et al, 2015; Zeev-Ben-Mordehai et al, 2015). We found that the majority of LOX cells formed abundant puncta at the late stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we focused on the arginine cluster in the gD cytoplasmic domain, since positively charged amino acid clusters in proteins have been reported to be involved in various protein functions, including binding to other proteins, membrane lipids, RNA, and DNA and regulation of subcellular localization (24)(25)(26)(27). We report here that the arginine cluster in the gD cytoplasmic domain is required for the efficient formation of microvilluslike projections at the plasma membrane of HSV-1-infected cells and for viral secondary envelopment in HSV-1-infected cells.…”
mentioning
confidence: 99%